Pengaruh Kombinasi Aromaterapi Esensial Lemon Dan Relaksasi Benson Terhadap Intensitas Dysmenorrhea Pada Remaja Putri - Fatma Jama; Sri Wahyuni; Nopi Nur Khasanah; Wahyu Endang Setyowati; Andi Masnilawati; Latifah Rahmawati Bauw (Window of Public Health Journal, 2026)
Dysmenorrhea is one of the most common complaints experienced by adolescent girls and can impact daily activities, concentration in school, and quality of life. Various non-pharmacological efforts have been developed to address dysmenorrhea, one of which is through a combination of lemon essential aromatherapy and Benson relaxation, which is known to provide a relaxing effect, reduce anxiety, and help reduce uterine muscle spasms. The mechanisms by which aromatherapy and relaxation techniques exert their effects involve modulation of the nervous system and reduced levels of stress-related hormones, which can contribute to decreased uterine contractions and reduced pain perception. This study aims to determine the effect of administering a combination of lemon essential aromatherapy and Benson relaxation on the intensity of dysmenorrhea in adolescent girls. This study used a pre-experimental design with a one-group pretest-posttest approach. The study sample consisted of 33 respondents selected using a purposive sampling technique. The intensity of dysmenorrhea was measured using a Numeric Rating Scale (NRS) before and after the intervention. Data were analyzed using the Wilcoxon test with a 95% confidence level (α = 0.05). The results showed a decrease in the intensity of dysmenorrhea after administering a combination of lemon essential aromatherapy and Benson relaxation. Before the intervention, the majority of respondents experienced moderate pain, while after the intervention, most respondents experienced mild pain, and some respondents no longer felt pain. The Wilcoxon test showed a p-value <0.05, indicating a significant effect of the combination of lemon essential aromatherapy and Benson relaxation on reducing dysmenorrhea intensity in adolescent girls. This study concluded that the combination of lemon essential aromatherapy and Benson relaxation was effective in reducing dysmenorrhea intensity in adolescent girls. Understanding the underlying mechanisms can help healthcare professionals better appreciate the potential benefits and optimize the implementation of this non-pharmacological approach.